Biopharma As a Potential Business for Urban Communities and Preservation of Community Heritage in Singkawang City: Biofarmaka sebagai Usaha Potensial Masyarakat Urban dan Pelestarian Warisan Masyarakat di Kota Singkawang - Ellyta, Ellyta; Ekawati; Rizieq, Rahmatullah; Bancin, Hardi Dominikus (Yayasan Ahmar Cendekia Indonesia, 2025)
Nowadays, urbanites are faced with various health challenges, such as stress, pollution, and unhealthy lifestyles. Natural-based prevention and treatment are one of the solutions. Efforts can be made to provide information and education to urban communities about biopharma and its benefits. The increasing public awareness of health also affects the use of herbal medicines derived from plants in a traditional way. The implementation method used in this activity is lecture, discussion, and practice. The utilization of home yards with the cultivation of biopharma plants can provide benefits to urban communities, as seen from the motivation of partners to try to process biopharma plants by processing them, and can be a potential business for urban communities. In addition, the utilization of biopharmaceutical plants is one of the efforts to preserve ancestor's heritage in terms of medicine.